SINERGITAS PELAKSANAAN VAKSINASI COVID-19 BAGI PENYANDANG DISABILITAS DI KABUPATEN SLEMAN PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Faiza, Bunga Fata (Jurnal Konstituen, 2023)
Increasing the spread and birth of new variants of the COVID-19 virus and becoming wider and covering all sectors of basic community life from this research. The ability of the community's immune system to fight infectious viruses (immunity) needs to be improved, especially for people with disabilities. So far, the implementation is still facing obstacles despite the issuance of a circular by the Indonesian Ministry of Health. Stakeholders in Sleman District are trying to overcome this.This study aims to analyze the synergy of implementing COVID-19 vaccination for Persons with Disabilities in Sleman Regency. Research method used is descriptive qualitative with an inductive approach. Data was collected by using interview, observation, and documentation techniques. The data analysis technique uses the stages of data reduction, data presentation, and verification. The results of the research and analysis show that the synergy between academia, business, community, government, and media has succeeded in realizing the acceleration of vaccination for persons with disabilities. The synergy that has been built has proven to give birth to greater strength. However, there are still obstacles that need to be solved, so that in the future the results obtained will increase. Stakeholders involved in the implementation of the acceleration of disability vaccination in Sleman Regency should make a written commitment to be accountable and legal before the law. Then, vaccination activities should be carefully planned from a long time ago so that future activities can run better. The synergy carried out by all actors in the implementation of COVID-19 vaccination for persons with disabilities in Sleman Regency in an effort to realize immunity can be said to be successful. This can be seen, because people with disabilities say that they feel helped by the facilities provided by the stakeholders.